Naringenin-Loaded TPGS Polymeric Nanosuspension: In-Vitro and In-Vivo Anti-Inflammatory Activity - Sumathi Rajamani; Tamizharasi Sengodan; Sivakumar Thangavelu; Nikhitha K Shanmukhan; Arun Radhakrishnan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Naringenin, (NAR) from Citrus grandis(L.) Osbeck, family Rutaceae, exhibit extensive pharmacological action, lacks significance in application due to low aqueous solubility approximately 0.214 mg/ml, which results in low bioavailability of 5.8%. Nanosuspension of NAR (NARNS) was prepared in our previous studies using high pressure homogenization adding various polymers. All these formulations were characterized and as a continuation of our work formulations was further evaluated for their anti-inflammatory activity by in-vitro and in-vivo methods. Denaturation of protein method and membrane stabilization methods were chosen for in-vitro evaluation. In-vivo studies performed were acute inflammatory studies (carrageenan-induced paw oedema) and chronic inflammatory studies (cotton pellet granuloma) on Wistar albino rats. The studies demonstrated that the NAR and NARNS at a dose of 50 mg/kg P.O. have a potent activity compared to the standard drug diclofenac. The percentage protection against inflammation exhibited by NARNS was highly significant compared to NAR.